Adsorption of Lubricant Waste by Porous Materials: A Review - Wathi, Ayu Fahimah Diniyah; Dewi, Shofrina Surya; El-Ridlo, Nuruddin Kafy; Wijayanti, Sukma Wahyu; Masbukhin, Faizal Akhmad Adi; Bikharudin, Ahmad (Walisongo Journal of Chemistry, 2023)
The rapid development of technology today cannot be separated from the role of various kinds of machines to produce or increase the use value of an item. The more the engine operates, the more lubricant is used. Lubricants are included in the category of B3 waste (Toxic Hazardous Materials) so that they have a negative impact on the environment. Nearly 50% of all mineral lubricants enter the environment and cause irreparable environmental damage due to direct contact with water and soil. One of the efforts that can be done to reduce the B3 content in used lubricants is adsorption using a porous adsorbent. This study aims to see the relationship between the physical and chemical properties of the adsorbent with the physical and chemical properties of the adsorbate. This research was conducted by studying the literature of scientific articles with related topics. The results showed that some contaminants such as organic compounds, inorganic species, soot, hydrocarbons, and ash can be adsorbed with various adsorbents, namely modified sawdust, bentonite, fly ash, activated carbon, activated alumina, and zeolite Y derived from kaolin.